A decade of governance innovation and gaps in poverty alleviation - Bautista, Victoria A. (Philippine Journal of Public Administration, 2006)
The first attempt to formulate a national agenda in fighting poverty was started during the term of President Ramos in 1995 with the adoption of the Social Reform Agenda (SRA). SRA unified different national offices to craft key programs in addressing the plight of the poor. With the brief stint of President Estrada in 1998. 2000, the National Anti-Poverty Action Plan (NAAA) was launched in mid-2000 which maintained many of the features of the SRA. NAAA was followed by Kapit Bisig Laban sa Kahirapan (KALAHI) program uunder the Macapagal Arroyo presidency. While retaining features of the SRA, KALAHI improved some of SRA features that were considered weak. Innovations have been made in combating poverty such as the shift from sectoral to intersectoral process in planning for poverty alleviation, sectoral to intersectoral structure in overseeing poverty alleviation programs, and harnessing the poor as targets for implementing anti-poverty projects. In spite of the gains, the downside has been witnessed which includes inconsistencies in policies, the changing name of programs of similar features, poor tracking of the use of resources, and poor monitoring of situation in communities.